Creative writing on gender and caste in Dalit autobiographies and biographies: a view from within - Md Moshabbir Alam (Creativity Studies)
This paper critically examines the oeuvre of Kaushalya Baisantry and Sharmila Rege, focusing on their creative writing, Twice Cursed (orig. Dohra Abhishaap, originally published in 1999) and Writing Caste/Writing Gender: Narrating Dalit Women’s Testimonios (originally published in 2006), respectively. The writings discuss the empirical reality of caste and gender-divided society. The difficulties and problems that come with being a member of a lower caste in society and being a woman primarily concentrate on gender and caste, which become subjects for investigation and analysis in everyday life. This contrasts standard academic debates regarding gender, which display an anxious curiosity about their own experiences. Critical content analysis is utilized to analyze the data. In order to analyze the intersectionality of gender and caste, several works have been combined. It examines the idea that being a woman and belonging to a lower caste is akin to having “twice cursed” on one’s life. However, autobiographies, biographies, and life narratives have attempted to challenge the hegemony of patriarchy and shed light on the oppression experienced in everyday life on the basis of gender and caste.